Peripheral blood markers predict immunotherapeutic efficacy in patients with advanced non-small cell lung cancer: A multicenter study - Liu, Shuai; Zhao, Liuyuan; Zhou, Guohua (Frontiers in Genetics, 2022)
This study aims to investigate the prognostic impact of peripheral blood markers in patients with advanced non-small cell lung cancer (NSCLC) undergoing immunotherapy. In the current multicenter study, 157 advanced NSCLC cases treated by immunotherapy at three institutions were included. Biochemical parameters in baseline peripheral blood were collected. The associations between biochemical parameters and prognosis were investigated by the Kaplan–Meier survival analyses and Cox regression, and the predictive performances of biomarkers were evaluated via receiver operating characteristic analysis. The neutrophil-to-lymphocyte ratio (NLR) (progression-free survival [PFS]: hazard ratio [HR], 1.766; 95% confidence interval [CI], 1.311–2.380; p < 0.001; overall survival [OS]: HR, 1.283; 95% CI, 1.120–1.469; p < 0.001) and red blood cell distribution width (RDW) (PFS: HR, 1.052; 95% CI, 1.005–1.102; p = 0.031; OS: HR, 1.044; 95% CI, 1.001–1.091; p = 0.042) were revealed as independent predictors for both PFS and OS. In addition, NLR ≥3.79 (1-year PFS, 24.2% [95% CI, 15.2%–38.4%] versus 27.3% [95% CI, 18.2%–41.1%], p = 0.041; 1-year OS, 44.2% [95% CI, 32.5%–60.1%] versus 71.8% [95% CI, 60.6%–85.2%], p < 0.001) or RDW ≥44.8 g/L (1-year PFS, 19.2% [95% CI, 11.4%–32.3%] versus 31.7% [95% CI, 21.9%–46.0%], p = 0.049; 1-year OS, 54.0% [95% CI, 42.7%–68.3%] versus 63.1% [95% CI, 50.6%–78.6%], p = 0.014) was significantly correlated to poorer PFS and OS than NLR < 3.79 or RDW <44.8 g/L. Moreover, NLR and RDW achieved areas under the curve with 0.651 (95% CI, 0.559–0.743) and 0.626 (95% CI, 0.520–0.732) for predicting PFS, and 0.660 (95% CI, 0.567–0.754) and 0.645 (95% CI, 0.552–0.739), for OS. Therefore, PLR and RDW could help predict the immunotherapeutic efficacy of advanced NSCLC.